2014
DOI: 10.3892/mco.2014.447
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and prognosis of mucinous gastric carcinoma

Abstract: Abstract. Mucinous gastric carcinoma (MGC) is a rare histological subtype of undifferentiated gastric carcinoma, accounting for ~2.6-6.6% of all gastric cancer cases. The clinicopathological characteristics and prognosis of MGC are controversial. The present study aimed to determine the clinicopathological characteristics and prognosis of patients with MGC. We retrospectively compared the characteristics and postoperative survival of 70 patients with MGC and 2,492 non-MGC (NMGC) cases who underwent surgical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…MGC is often found in a more advanced stage than NMGC, 7,16,17 which was also found in the present study. MGC is found mainly in advanced stages and is believed to be related to the characteristics of MGC.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…MGC is often found in a more advanced stage than NMGC, 7,16,17 which was also found in the present study. MGC is found mainly in advanced stages and is believed to be related to the characteristics of MGC.…”
Section: Discussionsupporting
confidence: 88%
“…The proportion of the initial pT4, M1 stage was also the highest in the MGC group. The MGC group had a significantly higher recurrence rate than the NMGC and SRC groups (37.3% in MGC vs. 16.8%…”
Section: Baseline Characteristicsmentioning
confidence: 89%
See 1 more Smart Citation
“…Lots of studies have reported on the clinical–pathological characteristics and prognosis of MGC, 4 , 6 , 7 , 18 but few have focused on the prognostic significance of mucinous component in gastric adenocarcinoma, even though the coexistence of mucinous component and gastric adenocarcinoma is observed frequently. Kim et al 19 revealed there were some differences in several clinicopathological features of signet-ring cell, mucinous (MGC), papillary, and lymphoepithelioma-like subtypes of advanced gastric cancer, and no statistical differences in survival were found among these after R0 gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“… 3 5 Tang et al 6 found that MGC was an aggressive malignancy with unique clinicopathological features in 244 MGC patients who underwent radical gastrectomy with D2 lymphadenectomy. In Isobe et al’s study, 7 70 MGC patients were compared with 2,492 non-MGC (NMGC) patients, and although MGC is rarer and mostly detected at an advanced stage, the diagnosis of the mucinous histological subtype was not an independent prognostic factor. Zhao et al’s results showed MGC was more likely to have large tumors and more advanced tumor stage (II and III) than NMGC, and the thicker gastric wall, layered enhancement pattern, and calcification were highly suggestive computed tomography features for differentiating MGC from NMGC.…”
Section: Introductionmentioning
confidence: 99%